2016
DOI: 10.1002/pc.24150
|View full text |Cite
|
Sign up to set email alerts
|

Vibration analysis of nanocomposite microplates integrated with sensor and actuator layers using surface SSDPT

Abstract: In the present work, nonlinear vibration analysis of polymeric nanocomposite microplates integrated with polyvinylidene fluoride (PVDF) layers as sensors and actuators is investigated. The middle layer is reinforced with carbon nanotubes (CNTs) and it's equivalent material properties are obtained by Mori–Tanaka approach. The nanocomposite and PVDF layers are subjected, respectively, to 2D magnetic and 3D electric fields. The system is rested on an elastic medium which is simulated with orthotropic Pasternak fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Piezoelectricity refers to the ability of certain materials to convert mechanical stress into electrical energy and vice versa by the following equations that relate the mechanical stress or strain to the resulting electric field or charge [33][34][35] :…”
Section: Piezoelectric Relationshipmentioning
confidence: 99%
See 1 more Smart Citation
“…Piezoelectricity refers to the ability of certain materials to convert mechanical stress into electrical energy and vice versa by the following equations that relate the mechanical stress or strain to the resulting electric field or charge [33][34][35] :…”
Section: Piezoelectric Relationshipmentioning
confidence: 99%
“…Piezoelectricity refers to the ability of certain materials to convert mechanical stress into electrical energy and vice versa by the following equations that relate the mechanical stress or strain to the resulting electric field or charge 33–35 : D=eijε+dijE σ=Cijε[]eitalicijTE where { D } is the electric displacement vector. [ e ij ] is the piezoelectric constant matrix.…”
Section: Theoretical Formulation Of Sandwich Platementioning
confidence: 99%
“…There was an increase in magnetic saturation (Ms) moment from PPy–Fe–AMP-20, PPy–Fe–AMP-40, and PPy–Fe–AMP-50 composites which were 3.8, 4.2, and 5.75 emu/g. Thus, it can be inferred that keeping the Fe concentration constant and increasing the AMP concentration increased the ferromagnetic behaviour [ 192 ]. Xiao et al synthesized PPy composites by four methods, adding magnetic additives, and found that the magnetic additives were responsible for the electromagnetic properties of the PPy composites.…”
Section: Properties Of Polypyrrole Compositementioning
confidence: 99%
“…Arani et al. [51] designed a PD controller for CNT/polymer plates located between piezoelectric PVDF faces and studied the active natural frequency of proposed smart structures. Using FEM and FSDT, Tao et al.…”
Section: Introductionmentioning
confidence: 99%